AESTHETIC OUTCOME OF SLIDING ISLAND FLAP FOR RECONSTRUCTION OF CHEEK AFTER TUMOUR ABLATION - ullah, Hidayat; ullah, Obaid; Asif, Mohammad; Tahir, Mohammad; Aslam, Mohammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: Skin cancer is the most common malignancy in humans and the incidence continues to rise. Facial reconstruction after cutaneous tumour ablation is a challenging job and needs thorough knowledge of the anatomy and physiology of face skin, biomechanics of skin and muscles, design of local flaps and their blood supply. The objective of this study was to report the aesthetic results of sliding island flap on the cheek. Methods: This study was carried in the department of Plastic and Reconstructive Surgery Postgraduate Medical Institute Hayatabad Medical Complex Peshawar from March 2001 to February 2004. Forty patients with age 50-70 years having Basal Cell Carcinoma on infraorbital and malar area of the cheek were taken for the study. Tumors were excised with safe margins and defects restored with sliding island flap. This flap is based on subcutaneous vertical pedicle that vascularizes the skin island through sub dermal plexus. Patients were regularly followed up with preoperative and postoperative photography. Final aesthetic results were analyzed after six months. Results: Good symmetry of cheek was achieved. There was no noticeable scarring. Flap necrosis was not seen in any patient. Only one patient had mild ectropion of the lower eyelid (2.5%) that did not need any revisional surgery. Conclusions: Relatively bigger defects of the cheek can be easily covered with this flap with preservation of cosmesis and without any distortion in the symmetry of the face. KEY WORDS: Cheek, Tumour, Reconstruction, Sliding island flap.